Distribution of Bacteriocin-like Substance-Producing Lactic Acid Bacteria in Egyptian Sources - Mohamed Abdelfattah Maky; Naoki Ishibashi; Xiao Gong; Kenji Sonomoto; Takeshi Zendo (Applied Microbiology)
Lactic acid bacteria (LAB) are known as producers of various antimicrobial compounds. Among these, bacteriocins have attracted considerable interest because of their potential use as natural food preservatives. The aim of this study was to identify potential strains from Egyptian sources that have unique antibacterial activity for possible future use. In this current study, 835 LAB strains were isolated from different Egyptian sources such as meat, salted fish, chicken byproducts, dairy products, and a starter for fermentation. The bacteriocin activity of cell-free culture supernatants was tested using the spot-on-lawn method against eight indicator strains. As a result, 237 isolates were found to produce bacteriocin-like substances (BLS). According to their antimicrobial spectra, they were classified into three groups: the broad spectrum group (2.1% of isolates), the middle spectrum group (15.2% of isolates), and the narrow spectrum group (82.7% of isolates). 16S rDNA sequencing showed that all isolates belonged to LAB strains such as Lactobacillus, Enterococcus, Carnobacterium, Weissella, and Leuconostoc. Egyptian materials were found to be promising sources of bacteriocin-producing LAB. The BLS generated from LAB in this current work have a diverse antimicrobial spectrum against numerous bacterial hazards, including Listeria. The new strains identified in this study were shown to have characteristic antimicrobial spectra and can be used in the future as effective preservatives in the food industry.